Role of Debt To Equity Ratio Mediating Effect Return On Assets and Current Ratio Against Firm Value - Sutriono Sutriono; Eka Nurmala Sari; Muis Fauzi Rambe (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2021)
The food and beverage sector in manufacturing companies has an important role for the Indonesian economy. This study aims to determine, test and analyze the Debt to Equity Ratio mediating the effect of Return On Assets and Current Ratio on Price to Book Value in Food and Beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. In this study using an associative approach. The sampling technique used is purposive sampling with a sample of 10 food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The data collection technique is documentation technique, in the form of secondary data by taking data from the Indonesian Stock Exchange website. The data analysis technique used is descriptive statistical test, and SEM (Structural Equation Modeling) analysis by testing the outer model analysis, inner model analysis, and mediating effect analysis. The results showed that Return On Assets had an effect on the Debt to Equity Ratio. Current Ratio affects the Debt to Equity Ratio. Return On Assets has an effect on Price to Book Value. Current Ratio has no effect on Price to Book Value. Debt to Equity Ratio has an effect on Price to Book Value. Debt to Equity Ratio can mediate the effect of Return On Assets on Price to Book Value. And the Debt to Equity Ratio can mediate the influence of the Current Ratio on Price to Book Value.